Evaluation of the microbiological contamination degree of the Paciência River estuary, Maranhão State - Oliveira, Dulce Raquel Pereira; Leal de Castro, Antonio Carlos; Soares, Leonardo Silva; Nascimento, Adenilde Ribeiro; Porto, Heliene Leite Ribeiro (Arquivos de Ciências do Mar, 2012)
The discharge of sewage into coastal marine waters and survival of pathogens in aquatic environment bring serious implications for public health of riparian populations residing in coastal regions. The Paciência River is one of the main water courses of the São Luís Island, having important contribution in the city water supply system. Currently, receives increased loads of domestic effluents along its course, compromising the quality of its waters. This work aims to assess the degree of microbiological contamination of water from the Paciência river estuary through quantification of total and thermotolerant coliform bacteria as well as count heterotrophic bacterial population. Bimonthly sampling was carried out from February, 2006 to February, 2007, collected in four sampling station chosen to represent a seaward gradient in land drainages and other effluents. Surface water temperatures, salinity, pH and dissolved oxygen were measured by multiparameter (Model HQ40d). It was noted that concentrations of total and fecal coliform bacteria were associated with the spatial heterogeneity of points sampled and the influence of vicinity of the sewage outfall. As such, the creeks Iguaíba, Grande and Christóvão subjected more intensely to the hydrodynamics of the estuarine environment showed values inside of microbiological standards recommended by current legislation, while the Igarapé Pindoba under lower tidal influence, showed greater coliform concentrations being considered no safe for recreacional purposes.